The empire is dead, long live the empire! Long-run persistence of trust and corruption in the bureaucracy - Sascha O. Becker; Katrin Boeckh; Christa Hainz; Ludger Woessmann (Center for Economic Studies and ifo Institute (CESifo), 2011)
Do empires affect attitudes towards the state long after their demise? We hypothesize that the Habsburg Empire with its localized and well-respected administration increased citizens' trust in local public services. In several Eastern European countries, communities on both sides of the long-gone Habsburg border have been sharing common formal institutions for a century now. Identifying from individuals living within a restricted band around the former border, we find that historical Habsburg affiliation increases current trust and reduces corruption in courts and police. Falsification tests of spuriously moved borders, geographic and pre-existing differences, and interpersonal trust corroborate a genuine Habsburg effect.
Keywords: N33; N34; D73; Z10; 330; Habsburg Empire; trust; corruption; institutions; borders; Kommunalverwaltung; Vertrauen; Korruption; Soziale Werte; Meinung; Südosteuropa; Ungarn; Institutionelle Infrastruktur; Österreich-Ungarn